Microfiltración marginal de las resinas Filtek Z 350 (flowable restorative), Filtek Z 250 (univesal restorative), Filtek P 60 (posterior restorative), en cavidades clase II mediante el uso de dos técnicas de obturación, estudio In Vitro: período noviembre del 2012 - abril 2013. - Lafebre N., Ruth A. (2013)
The marginal microleakage is defined as the step not clinically detectable bacteria, fluids, molecules or ions between a wall cavity and the restorative material causing discoloration and deterioration of the margins of the restoration, secondary caries in the tooth-restoration interface, hypersensitivity of the restored tooth and the development of pulpar pathologies. A study was conducted in vitro in which to assess in degree of marginal microleakage of composite resins Filtek Z350 (flowable restorative), Filtek Z250 (universal restorative), Filtek P60 (later restorative), in class II cavities (according to the classification of black) through the use of two filling techniques, incremental technique and block. In this study were used 32 newly extracted human premolars and preserved in physiological saline during the entire period of work. There were 4 groups of 8 dental pieces in each; these in turn were divided into 2 subgroups of 4 parts and 2 dental cavities in each piece. After the restoration process was submitted to the parts to the coloring of methylene blue by 96 hours after the court and measurement of the microfiltration. The data more low was obtained in the groups restored with Z350-P60 incremental technique with a value of 0.0mm, while the highest value on the same wall is the group technical Z250 in block data with a 2.92mm. On the other hand in the gingival wall the highest value was 2.37mm of the group Z350-Z250 block and the lowest value was 1.08mm in the group Z350-Z250 incremental. Key words: Microfiltration, resin and restoration techniques.